The Golden Spiral Flap: A New Flap Design that Allows for Closure of Larger Wounds under Reduced Tension – How Studying Nature’s Own Design Led to the Development of a New Surgical Technique - Paul, Sharad P. (Frontiers in Surgery, 2016)
This paper details the study of biodynamic excisional skin tension lines on the scalp, and the development of a new flap technique for closure of scalp wounds. Recently, a study by this author, on pigskin, replicated whorls by placing tissue under rapid stretch using saline tissue expanders, by re-creating rapid dermo-epidermal shear of skin – thereby concluding that the golden spiral pattern is nature’s own pattern for rapid expansion. Given the relationship between tissue expansion and stretch have been shown to cause deformation gradients that have both elastic and growth factors, the author set out to test the hypothesis that a golden spiral pattern therefore would be more efficient at closing wounds under less tension when compared to standard semicircular rotational flap patterns. The author conducted a series of experiments, both on pigskin (to first confirm the hypothesis, using a recently developed computerized tensiometer) and later a clinical study. This paper presents a new random pivotal flap technique for skin closures on the head and neck: The Golden Spiral Flap. Biomechanics, planning and advantages of this new flap are described in this paper.